1976
DOI: 10.1111/j.1600-0528.1976.tb00961.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐caries effect of a 2% Na2PO3F‐dentifrice in a Danish fluoride area

Abstract: A 3-year experimental toothbrushing study was conducted in a natural fluoride area in Denmark to evaluate the anti-caries effect of a 2% sodium monofluorophosphate dentifrice. In a previous report the results for the total population of 1,407 schoolchildren, representing a broad age-span (7-12 years), at the commencement of the study in 1970 were given. In the present report results are presented for two subpopulations of "8-year-olds" and "11-year-olds" at the commencement of the study. Differential analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…using sodium monofluorophosphate dentifrice reported a 30% reduction in dental caries increments and 27.9% and 28.2% reduction in DMFT and DMFS values, respectively. [ 16 ] The results of the study are in accordance with the results reported by Leo Hanachowicz, Lind and Anlow.…”
Section: Discussionsupporting
confidence: 91%
“…using sodium monofluorophosphate dentifrice reported a 30% reduction in dental caries increments and 27.9% and 28.2% reduction in DMFT and DMFS values, respectively. [ 16 ] The results of the study are in accordance with the results reported by Leo Hanachowicz, Lind and Anlow.…”
Section: Discussionsupporting
confidence: 91%
“…The concentration of fluoride in dentifrices tested most frequently in clinical trials has been 1,000 parts per million (ppm), usually as sodium monofluorophosphate (MFP). Many studies have been done with higher than conventional concentrations of fluoride, r a n p g from 1,450 to 2,800 pprn of fluoride (41)(42)(43)(44)(45)(46)(47). Ripa (47) recently reviewed these studies.…”
Section: Effectiveness Of Toothpastes With Lower-thanconventional Flumentioning
confidence: 99%
“…Currently marketed over-the-counter fluoride dentifrices contain about 1000 ppm fluoride. Studies have generally shown positive results when evaluating the higher fiuoride dentifrices (2)(3)(4)(5)(6)(7)(8)(9). Higher concentrations of fiuoride delivered from other vehicles, such as topical gels and solutions, have produced excellent results in the prevention of caries but are available only by prescription.…”
mentioning
confidence: 99%